Notes to Philosophy 167: Class 2 -- 16th Century Astronomy: Copernicus and Tycho Brahe -- Part 10. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Copernicus's Triangulated Distances of the Planets -- Philosophic Issue: Grounds for Preferring It?; Generally corresponds to the video segment: Class 2, Part 10.